KEBIJAKAN PENDIDIKAN PADA ADAPTASI KEBIASAAN BARU DI SDIT INSAN KARIMA RANGKASBITUNG - Mumu Zainal Mutaqin (LPPM Universitas Bina Bangsa, 2022)
This study aims to create maximum learning outcomes and can improve teacher competence by using technology. In addition, teachers can have internal competencies that can support the teaching process. The education policy at SDIT Insan Karima uses an online and offline learning approach. And can increase students' motivation to understand using technology tools well. And online and offline learning policies make it a challenge to carry out learning using technology. Learning during the adaptation period of new habits has difficulty in understanding and using the abilities of hearing, speaking, reading, writing, and thinking. Online learning is a learning activity that utilizes the Whatsapp group network, telegrams and assignments as a method of delivery, interaction and facilities and is supported by various other forms of learning services